Bioconversion of glycerol into lipids by Rhodosporidium toruloides in a two‐stage process and characterization of lipid properties. Issue 3 (16th August 2016) - Xu, Jingyang; Zhao, Xuebing; Du, Wei; Liu, Dehua
Abstract : Rhodosporidium toruloides AS 2.1389 has been considered a promising oleaginous strain due to its flexible substrate adaptability, high lipid content, and coproduction of some pigments. In previous work, R. toruloides has shown good potential to directly convert crude glycerol into intracellular lipids. However, the difference in nutritional demand between cell growth and lipid accumulation was found to be a dilemma. Therefore, a glycerol‐based two‐stage process was proposed in the present work to separately meet the nutritional demand of both the cell proliferation phase and lipid accumulation phase. Factors that affect microbial conversion of glycerol into lipid were investigated, statistically analyzed, and optimized. As a result, 26.5 g L −1 biomass with 10 g L −1 lipid was obtained in the two‐stage process. Lipid yield (0.20 g g −1 ) and productivity (0.083 g L −1 h −1 ) achieved were significantly higher than the previously optimized batch culture. In R. toruloides lipids, the dominant fatty acid compositions are palmitic acid (28.5%), stearic acid (12.9%), oleic acid (41.3%), and linoleic acid (12.8%). Phospholipids accounts for 0.63% in total lipid. Lipase‐catalyzed methanolysis could achieve up to 95% biodiesel yield. The characterization of R. toruloides lipid suggests its great application potential for biodiesel and specialty‐type lipid products.